Alexander's army - D'Lacey, Chris (D'Lacey, Chris. UNICORNE files, 2015)
Michael Malone is assigned to investigate a local comic shop by the mysterious UNICORNE agency because they are displaying a comic book with a disturbingly familiar heroine--but he soon realizes that the sinister shop hides an invisible army come to life, with a menacing maniac at its head, and worse he does not know if he can trust his fellow agents.